PERAN GENDER DAN STRATEGI BERTAHAN HIDUP KELUARGA BURUH PABRI UNTUK MEMENUHI KEBUTUHAN HIDUP KELUARGA (Studi Kasus di Pabrik Karet PTPN XII Kebun Mumbul Kecamatan Mumbulsari Kabupaten Jember) - Annisa Trya Puspitasari; Diah Puspaningrum (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2019)
Workers in the rubber factory PTPN XII Kebun Mumbul there are male and female workers who have differences, both biologically and genetically. These differences will form a role that can be seen from the activities of workers and families. The labor income which is relatively low compared to the expenditure of family needs every month makes the family of rubber factory workers implement a survival strategy to meet the family's living needs. This study aims to determine: (1) the gender role that is found in the families of rubber factory workers in PTPN XII Kebun Mumbul, (2) the survival strategies of rubber factory workers' families in PTPN XII Kebun Mumbul. Determination of the research area using a purposive method, namely PTPN XII Kebun Mumbul Rubber Factory. The method of determining informants is done intentionally or purposive sampling using certain considerations. The data used are primary and secondary data using data collection methods such as interviews, observation and document study. The data is then analyzed using Gender Framework Analysis (GFA) and Miles and Huberman analysis. The results showed that 1) The role of husband and wife in the rubber factory worker family there are productive, reproductive and social roles. The productive role is played by husband and wife, the reproductive and social role is played by the wife. In emik's view, it is common and common for wives to work, the gender issue that exists in rubber factory workers' families is that the workload is heavier. (2) Survival strategies carried out by rubber factory workers 'families, namely (a) alternative self-help subsystems, actions taken with abilities, businesses or resources owned by rubber factory workers' families to work both husband and wife, (b) Frugality by means of saving and minimizing expenditure, and (c) Networking strategies by utilizing social networks in the surrounding environment.